Radiosynthesis of the iodine‐124 labeled Hsp90 inhibitor PU‐H71. (25th January 2016) - Taldone, Tony; Zatorska, Danuta; Ochiana, Stefan O.; Smith‐Jones, Peter; Koziorowski, Jacek; Dunphy, Mark P.; Zanzonico, Pat; Bolaender, Alexander; Lewis, Jason S.; Larson, Steven M.; Chiosis, Gabriela; Pillarsetty, Naga Vara Kishore
Abstract : Heat shock protein 90 (Hsp90) is an ATP dependent molecular chaperone protein whose function is critical for maintaining several key proteins involved in survival and proliferation of cancer cells. PU‐H71 (1), is a potent purine‐scaffold based ATP pocket binding Hsp90 inhibitor which has been shown to have potent activity in a broad range of in vivo cancer models and is currently in Phase I clinical trials in patients with advanced solid malignancies, lymphomas, and myeloproliferative neoplasms. In this report, we describe the radiosynthesis of [ 124 I]‐PU‐H71(5); this was synthesized from the corresponding Boc‐protected stannane precursor 3 by iododestannylation with [ 124 I]‐NaI using chloramine‐T as an oxidant for 2 min, followed by Boc deprotection with 6 N HCl at 50 °C for 30 min to yield the final compound. The final product 5 was purified using HPLC and was isolated with an overall yield of 55 ± 6% ( n = 6, isolated) from 3, and >98% purity and an average specific activity of 980 mCi/µmol. Our report sets the stage for the introduction of [ 124 I]‐PU‐H71 as a potential non‐invasive probe for understanding biodistribution and pharmacokinetics of PU‐H71 in living subjects using positron emission tomography imaging. Abstract : PU‐H71 (1 ) is a potent purine‐scaffold based ATP pocket binding Hsp90 inhibitor which has been shown to have potent activity in a broad range of in vivo cancer models and is currently in Phase I clinical trials. In this report, we describe the radiosynthesis of [ 124 I]‐PU‐H71 (5 ) in four steps from1 . Our report sets the stage for the introduction of [ 124 I]‐PU‐H71 as a potential non‐invasive probe for understanding biodistribution and pharmacokinetics of1 in living subjects using positron emission tomography imaging.